IFAS Assessment of Non-native Plants in Florida's Natural Areas: Status Assessment - Alison M. Fox; Doria R. Gordon; Joan A. Dusky; Linda Tyson; Randall K. Stocker; Kenneth A. Langeland; Aimee L. Cooper (EDIS)
Revised! SS-AGR-225, a 14-page publication by Alison M. Fox, Doria R. Gordon, Joan A. Dusky, Linda Tyson, Randall K. Stocker, Kenneth A. Langeland, and Aimee L. Cooper, is the component of the IFAS Assessment that provides evaluations of plants that currently occur within Florida. designed to identify those non-native plant species that are invasive in areas of Florida where designated management objectives include the conservation of native biodiversity. Includes references. Published by the UF Department of Agronomy, April 2009.